Anti-slavery and Australia : no slavery in a free land? - Lydon, Jane, 1965- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Bringing the histories of British anti-slavery and Australian colonization together changes our view of both. This book explores the anti-slavery movement in imperial scope, arguing that colonization in Australasia facilitated emancipation in the Caribbean, even as abolition powerfully shaped the Settler Revolution. The anti-slavery campaign was deeply entwined with the administration of the empire and its diverse peoples, as well as the radical changes demanded by industrialization and rapid social change in Britain. Abolition posed problems to which colonial expansion provided the answer, intimately linking the end of slavery to systematic colonization and Indigenous dispossession. By defining slavery in the Caribbean as the opposite of freedom, a lasting impact of abolition was to relegate other forms of oppression to lesser status, or to deny them. Through the shared concerns of abolitionists, slave-owners, and colonizers, a plastic ideology of 'free labour' was embedded within post-emancipation imperialist geopolitics, justifying the proliferation of new forms of unfree labour and defining new racial categories. The celebration of abolition has overshadowed post-emancipation continuities and transformations of slavery that continue to shape the modern world"--
Introduction. 'An equal portion of liberty' -- No slavery in a free land? -- 'Poor creatures'. Antislavery and transportation, 1789-1807 -- In spite of all the Saints, 1807-1833 -- Abolition, systematic colonization, and the end of transportation, 1830-1840 -- Is not the New Hollander a man and a brother? Abolition and Genocide -- Anti-slavery in Australia after Emancipation, 1834-1900. 'We but enliven labour with the lash' -- Modern Slavery and Australia.
OCLC-licensed vendor bibliographic record.
Keywords: Antislavery movements -- Australia -- History; Slavery -- Australia -- History; Australia -- Colonization -- History; HISTORY / General; HISTORY / Australia & New Zealand; HISTORY / Europe / Great Britain